Comparison of phenylephrine, ephedrine, and norepinephrine for the prevention and treatment of spinal-induced hypotension in pre-eclamptic patients undergoing caesarean section: A systematic review and network meta-analysis - Ahmed S. Badran; Karim S. Shata; Ahmed Elgammal; Ahmed A. Samir; Mostafa O. Farag; Salma Allam; Ahmed Samy (Indian Journal of Anaesthesia)
Background and Aims: Spinal-induced hypotension in parturients with pre-eclampsia (PE) can lead to adverse perinatal outcomes, making effective prophylaxis and treatment crucial. We aim to compare the prophylactic and therapeutic roles of phenylephrine, ephedrine, and norepinephrine (NE) in treating post-spinal hypotension in PE patients. Methods: We conducted a comprehensive search of various databases up to June 2024, focusing on randomised clinical trials (RCTs). Standardised mean differences (SMDs) were used for continuous outcomes, while odds ratios (ORs) were employed for binary outcomes. Analyses were performed using R with both fixed-effect and random-effects models. Results: Nine RCTs (804 patients) were included in the analysis. Therapeutic comparisons revealed no differences in mean arterial pressure between NE and ephedrine (SMD = 0.51, 95% CI: −0.49, 1.53) or phenylephrine and ephedrine (SMD = 0.90, 95% CI: −0.01, 1.82). Phenylephrine was associated with a significantly higher risk of bradycardia compared to ephedrine (OR = 14.34, 95% CI: 1.8, 113.64, P = 0.018), whereas NE showed an insignificant difference (OR = 2.54, 95% CI: 0.27, 23.94). NE significantly improved the umbilical artery pH compared to ephedrine (SMD = 0.32, 95% CI: 0.02, 0.62, P = 0.036). No significant differences were identified in nausea or vomiting. Prophylactic comparisons revealed no significant differences between phenylephrine and NE for hypotension (OR = 0.98, 95% CI: 0.22, 4.26). For bradycardia, no difference was observed between NE and ephedrine (OR = 0.08, 95% CI: 0.002, 3.33) or phenylephrine and ephedrine (OR = 0.19, 95% CI: 0.006, 74). Conclusions: Phenylephrine, ephedrine, and NE exhibit comparable haemodynamic effects and maternal side effects, although phenylephrine increases the risk of bradycardia. NE improves umbilical artery pH.